Solid electrolyte and application thereof
By forming a lithium carbonate coating on the surface of the sulfide electrolyte, the problem of poor stability of the sulfide electrolyte on the oxide positive electrode and air is solved, and the cycle life and safety of the all-solid-state battery are improved.
Patent Information
- Application Number
- CN202411824431.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
The sulfide electrolyte has poor stability on the oxide positive electrode and air, which affects the cycle life and safety of all-solid-state batteries.
A cladding layer is formed on the surface of the sulfide electrolyte, and the material of the cladding layer includes lithium carbonate, which is formed by exposure in pure CO2 and heating.
It improves the stability of solid electrolyte on the oxide positive electrode and air, extends the cycle life of the battery, and improves the stability and safety of the battery.
Smart Images

Figure CN119627192A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly to a solid electrolyte and its application. Background Art
[0002] As a kind of solid electrolyte, sulfide electrolyte has the advantages of high ionic conductivity, wide electrochemical window and good mechanical properties, and is considered as a key material to improve the energy density and cycle life of batteries. However, in practical applications, the sulfide electrolyte has poor stability against oxide cathodes and air, which affects the cycle life and safety of all-solid-state batteries, and severely restricts the further development and application of batteries. Summary of the Invention
[0003] The present invention provides a solid electrolyte and its application. By using the solid electrolyte and its application provided by the present invention, the stability of the solid electrolyte against oxide cathodes and air can be improved, thereby enhancing the cycle life, stability and safety of the battery.
[0004] To solve the above technical problems, the present invention provides a solid electrolyte, which at least includes:
[0005] A sulfide electrolyte; and
[0006] A coating layer, disposed on the surface of the sulfide electrolyte, and the material of the coating layer includes lithium carbonate;
[0007] Wherein, after the solid electrolyte is exposed to humid air with a dew point temperature of -40°C for 24 hours, the retention rate of ionic conductivity is 56% to 95%.
[0008] In an embodiment of the present invention, the chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , wherein, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from at least one of Cl, Br or I.
[0009] In an embodiment of the present invention, M is selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is 0 < b ≤ 0.1.
[0010] In an embodiment of the present invention, the chemical formula of the sulfide electrolyte is Li f P 1-g E g S wO g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, or Pb, and Q is selected from at least one of Cl, Br, or I.
[0011] In one embodiment of the present invention, E is Mg, Q is Cl, and the value range of g is 0.01 ≤ g ≤ 0.1.
[0012] In one embodiment of the present invention, the thickness of the coating layer is 1 nm to 200 nm.
[0013] In one embodiment of the present invention, the solid electrolyte is obtained by the following method:
[0014] Providing a sulfide electrolyte; and
[0015] Exposing the sulfide electrolyte to pure CO 2 and heating to form a coating layer on the surface of the sulfide electrolyte to obtain the solid electrolyte.
[0016] In one embodiment of the present invention, the pressure of the pure CO 2 is 0.01 MPa to 10 MPa, the exposure time of the sulfide electrolyte in the pure CO 2 is 0.1 h to 24 h, and the heating temperature is 0 to 200 °C.
[0017] The present invention also provides a all-solid-state battery, comprising at least:
[0018] A positive electrode sheet;
[0019] A negative electrode sheet; and
[0020] A solid electrolyte membrane disposed between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane includes the above-mentioned solid electrolyte.
[0021] The present invention also provides an electronic device, comprising the above-mentioned all-solid-state battery.
[0022] In summary, the present invention proposes a solid electrolyte and its application, which can effectively prevent the transmission of electrons between the sulfide electrolyte and the positive electrode material by improving the solid electrolyte in the all-solid-state battery and forming a coating layer on the surface of the sulfide electrolyte, thereby avoiding the interface reaction between the sulfide electrolyte and the positive electrode material, improving the stability of the solid electrolyte to the positive electrode, thereby improving the cycle life, stability and safety of the all-solid-state battery, and preventing the sulfide electrolyte from directly contacting with moisture and oxygen in the air, avoiding the reaction of the sulfide electrolyte with moisture and oxygen in the air, improving the stability of the solid electrolyte to the air, thereby further improving the cycle life of the battery. The sulfide electrolyte can improve the interface stability between the solid electrolyte and the negative electrode, ensure a continuous and stable lithium ion transmission channel, reduce the interface impedance, and improve the charge transfer efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 This is a graph showing the results of a room temperature cycle performance test on the all-solid-state battery in Example 3 of the present invention. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0026] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0027] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] The present invention provides a solid electrolyte, which includes, for example, a sulfide electrolyte and a coating layer, etc. Among them, the coating layer is disposed on the surface of the sulfide electrolyte, and its material includes, for example, lithium carbonate. After the solid electrolyte is exposed to humid air with a dew point temperature of -40°C for 24 hours, the retention rate of the ionic conductivity is, for example, 56% to 95%. In the solid electrolyte provided by the present invention, by providing the coating layer, it is possible to effectively prevent the transfer of electrons between the sulfide electrolyte and the positive electrode material, avoid the interfacial reaction between the sulfide electrolyte and the positive electrode material, improve the stability of the solid electrolyte to the positive electrode, thereby improving the cycle life, stability and safety of the all-solid-state battery. Moreover, the coating layer can prevent the sulfide electrolyte from directly contacting with moisture and oxygen in the air, avoid the reaction between the sulfide electrolyte and moisture and oxygen in the air, improve the stability of the solid electrolyte to air, and thus further improve the cycle life of the battery.
[0029] In an embodiment of the present invention, the sulfide electrolyte can improve the interfacial stability between the solid electrolyte and the negative electrode, ensure a continuous and stable lithium ion transmission channel, reduce the interfacial impedance, and improve the charge transfer efficiency. Specifically, the chemical formula of the sulfide electrolyte is, for example, selected from Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z and at least one of the like. Among them, in Li a P 1- b M b S c O d X e 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, etc., and X is selected from at least one of Cl, Br or I, etc. Further, M is, for example, selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is, for example, 0 < b ≤ 0.1. More specifically, when M is, for example, a +5 valence element, b is, for example, 0.04, and when M is, for example, a +3 valence element, b is, for example, 0.02. By controlling the types of M and X elements in the sulfide electrolyte and the value range of b, the stability of the solid electrolyte and the cycle performance of the battery can be improved, and thus the service life of the battery can be extended.
[0030] In an embodiment of the present invention, when the chemical formula of the sulfide electrolyte is Lif P 1-g E g S w O g Q z When 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is, for example, selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, etc., and Q is, for example, selected from at least one of Cl, Br, I, etc. Further, E is, for example, Mg, Q is, for example, Cl, and the value range of g is, for example, 0.01 ≤ g ≤ 0.1. Specifically, g is, for example, 0.02. By controlling the type of E element, the type of Q element, and the value range of g in the sulfide electrolyte, the stability of the solid electrolyte and the cycling performance of the battery can be improved, thereby extending the service life of the battery.
[0031] In an embodiment of the present invention, the material of the coating layer includes lithium carbonate, etc. Due to the high electrochemical stability and chemical stability of lithium carbonate, the coating layer can form a stable protective layer on the surface of the sulfide electrolyte. On the one hand, it can effectively prevent the transmission of electrons between the sulfide electrolyte and the positive electrode material, avoid the interfacial reaction between the sulfide electrolyte and the positive electrode material, improve the stability of the solid electrolyte to the positive electrode, and thus improve the cycling life, stability, and safety of the all-solid-state battery. On the other hand, it can prevent the direct contact between the sulfide electrolyte and moisture and oxygen in the air, avoid the reaction between the sulfide electrolyte and moisture and oxygen in the air, improve the stability of the solid electrolyte to the air, and thus further improve the cycling life of the battery.
[0032] In an embodiment of the present invention, the thickness of the coating layer is, for example, 1 nm to 200 nm, and the retention rate of the ionic conductivity of the solid electrolyte after being exposed to humid air with a dew point temperature of -40° for 24 h is, for example, 56% - 95%. By controlling the thickness of the coating layer, the stability of the solid electrolyte to air and the positive electrode can be improved, and at the same time, problems such as a decrease in the conductivity of the solid electrolyte caused by an excessive thickness of the coating layer can be avoided, thereby improving the cycling performance of the battery.
[0033] In an embodiment of the present invention, when preparing the solid electrolyte, first, in an atmosphere of an inert gas such as argon, according to the chemical formula of the sulfide electrolyte Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z, Li source, P source, M source, S source and X source, or Li source, P source, E source, S source and Q source are mixed evenly according to stoichiometric ratio, for example, placed in a ball mill for ball milling to obtain a precursor powder, and then the precursor powder is annealed and sintered at high temperature to obtain a sulfide electrolyte. Wherein, the Li source is, for example, selected from Li 2 At least one of S, LiCl, LiBr or LiI, etc., the P source is, for example, P 2 S 5 , M source is, for example, an oxide of M, S source is, for example, at least one of a Li source or a P source, X source is, for example, a Li source, E source is, for example, an oxide of E, Q source is, for example, a Li source, the ball-to-material mass ratio is, for example, (1-100):1, the ball milling time is, for example, 1h-48h, the rotation speed is, for example, 50rpm-1500rpm, the sintering temperature is, for example, 400℃-600℃, and the sintering time is, for example, 1h-48h.
[0034] In one embodiment of the present invention, after obtaining the sulfide electrolyte, the sulfide electrolyte is exposed to pure CO 2 Neutralization and heating, CO 2 It reacts with the lithium in the sulfide electrolyte to form a lithium carbonate coating on the surface of the sulfide electrolyte to obtain a solid electrolyte. 2 The pressure is, for example, 0.01 MPa to 10 MPa. The sulfide electrolyte is in pure CO 2 The exposure time is, for example, 0.1 h to 24 h, and the heating temperature is, for example, 0 to 200° C. Through the gas-solid reaction, a coating layer can be quickly formed on the surface of the sulfide electrolyte, thereby improving the preparation efficiency of the solid electrolyte, simplifying the preparation method of the solid electrolyte, reducing the preparation cost, and accelerating the industrialization process of the all-solid-state battery.
[0035] The present invention also provides an all-solid-state battery, for example, including a positive electrode plate, a negative electrode plate and a solid electrolyte membrane. The solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane is obtained by cold pressing the above-mentioned solid electrolyte under a pressure of 300MPa to 400MPa, and the thickness of the solid electrolyte membrane is, for example, 100μm to 500μm. In the present invention, the all-solid-state battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the types and types of the all-solid-state battery.
[0036] In one embodiment of the present invention, the positive electrode plate includes, for example, a positive electrode active layer, and the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a conductive agent, and a binder. Among them, the present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the conductive agent, and the binder, which can be selected according to actual needs. In other embodiments of the present invention, in addition to the positive electrode active layer, the positive electrode plate may also include a positive electrode collector, and the positive electrode collector is coated with a positive electrode active layer on the surface of at least one side. Among them, the positive electrode collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0037] In one embodiment of the present invention, in the positive electrode active layer, the positive electrode active material is selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA), etc., the positive electrode electrolyte is, for example, the solid electrolyte provided by the present invention, the conductive agent is selected from at least one of graphite, graphene, conductive carbon black (Super P), nanocarbon fiber (vapor-grown carbonfiber, VGCF) or carbon nanotubes, etc., and the binder is selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylpyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAN), etc. At least one of polyol, polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, fluorine rubber, β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer.
[0038] In one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O 2The positive electrode electrolyte is, for example, the solid electrolyte provided by the present invention, the conductive agent includes, for example, SuperP and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1, and the binder is, for example, PTFE. After the positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are uniformly mixed in a mass ratio of, for example, 69:29:1:1, the positive electrode sheet is directly obtained by dry pressing.
[0039] In another embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The positive electrode electrolyte is, for example, the solid electrolyte provided by the present invention, the conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1, and the binder is, for example, PTFE. The positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are mixed evenly, for example, in a mass ratio of 69:29:1:1, and then rolled and covered on the surface of the aluminum foil to obtain a positive electrode sheet.
[0040] In one embodiment of the present invention, the negative electrode plate is selected from at least one of a metal lithium plate, a metal indium plate or a lithium indium alloy plate. In other embodiments of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector. Among them, the negative electrode current collector is, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector or a stainless steel current collector, and the negative electrode active layer includes, for example, a negative electrode active material, a negative electrode electrolyte, a conductive agent and a binder. The present invention does not limit the mass ratio of the negative electrode active material, the negative electrode electrolyte, the conductive agent and the binder, and can be selected according to actual needs.
[0041] In one embodiment of the present invention, the negative electrode active material is selected from at least one of graphite materials or silicon materials, the negative electrode electrolyte is, for example, a sulfide solid electrolyte, the conductive agent is selected from at least one of graphite, graphene, SuperP, VGCF or carbon nanotubes, and the adhesive is selected from at least one of PVDF, CMC, SBR, PVP, PMMA, PAN, PAA, polyurethane, PVA, Alg, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-CDp, LA132, PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer.
[0042] In one embodiment of the present invention, the negative electrode current collector is, for example, a copper foil current collector, the negative electrode active material is, for example, silicon, the negative electrode electrolyte is, for example, a sulfide solid electrolyte, the conductive agent is, for example, SuperP, and the binder is, for example, PTFE. The negative electrode active material, the negative electrode electrolyte, the conductive agent, and the binder are mixed evenly in a mass ratio of, for example, 72:20:5:3, and then rolled and covered on the surface of the copper foil current collector to obtain a negative electrode sheet.
[0043] In one embodiment of the present invention, the above-mentioned positive electrode sheet, solid electrolyte membrane and negative electrode sheet are sequentially stacked, packaged, hot pressed and cold pressed to assemble into an all-solid-state battery. The assembly process of the all-solid-state battery is completed in an inert atmosphere glove box.
[0044] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0045] Example 1
[0046] Preparation of sulfide electrolyte: 2 mol of Li 2 S, 1.5 mol LiCl, 0.48 mol P 2 S 5 and 0.02 mol of Sb 2 O 5 The precursor powder was added to a ball mill for high-energy ball milling to obtain a precursor powder, wherein the ball-to-material ratio was 30:1, the rotation speed was 500 rpm, and the ball milling time was 20 h. After the ball milling, the precursor powder was sintered at 500 ° C for 10 h to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide electrolytes.
[0047] Preparation of solid electrolyte: Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide electrolyte in pure CO at a pressure of 1 MPa 2 The solid electrolyte was obtained by exposing the electrolyte to 150 °C for 0.1 h.
[0048] Preparation of solid electrolyte membrane: The solid electrolyte prepared above was cold pressed at 350 MPa to obtain a 300 μm solid electrolyte membrane.
[0049] Preparation of positive electrode: LiNi0.8 Co 0.1 Mn 0.1 O 2 The positive electrode active material, the solid electrolyte prepared above, the conductive agent and PTFE are mixed evenly in a mass ratio of 69:29:1:1, for example, and then the positive electrode sheet is obtained by dry pressing, and cut into a disc with a diameter of 10 mm. The conductive agent includes Super P and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1.
[0050] Choice of negative electrode: Choose metallic lithium as the negative electrode.
[0051] Battery preparation: The positive electrode sheet, solid electrolyte membrane and negative electrode sheet are stacked, packaged, hot pressed and cold pressed in sequence to assemble into an all-solid-state battery.
[0052] Example 2
[0053] The difference between this embodiment and embodiment 1 is that the sulfide electrolyte is in pure CO 2 The exposure time is 0.5h.
[0054] Example 3
[0055] The difference between this embodiment and embodiment 1 is that the sulfide electrolyte is in pure CO 2 The exposure time was 1 h.
[0056] Example 4
[0057] The difference between this embodiment and embodiment 1 is that the sulfide electrolyte is in pure CO 2 The exposure time was 10 h.
[0058] Example 5
[0059] The difference between this embodiment and embodiment 1 is that the sulfide electrolyte is in pure CO 2 The exposure time is 24h.
[0060] Example 6
[0061] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.99 Sb 0.0 1 S 4.475 O 0.025 Cl 1.5 The raw material is 2 mol of Li 2 S, 1.5 mol LiCl, 0.495 mol P 2 S 5 and 0.05 mol Sb2 O 5 .
[0062] Example 7
[0063] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 The raw material is 2 mol of Li 2 S, 1.5 mol LiCl, 0.47 mol P 2 S 5 and 0.03 mol of Sb 2 O 5 .
[0064] Example 8
[0065] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 The raw material is 2 mol of Li 2 S, 1.5 mol LiCl, 0.45 mol P 2 S 5 and 0.05 mol Sb 2 O 5 .
[0066] Example 9
[0067] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.96 Sb 0.0 4 S 4.40 O 0.10 Cl 1.3 Br 0.1 I 0.1 The raw material is 2 mol of Li 2 S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.48 mol P 2 S 5 and 0.02 mol of Sb 2 O 5 .
[0068] Example 10
[0069] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.52 P 0.99 In 0.0 1 S 4.485 O 0.015 Cl 1.5 The raw material is 2.01 mol of Li 2 S, 1.5 mol LiCl, 0.495 mol P 2 S 5 and 0.005 mol In 2 O 3 .
[0070] Embodiment 11
[0071] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 In 0.0 2 S 4.47 O 0.03 Cl 1.5 The raw material is 2.02 mol of Li 2 S, 1.5 mol LiCl, 0.49 mol P 2 S 5 and 0.01 mol In 2 O 3 .
[0072] Example 12
[0073] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.62 P 0.94 In 0.0 6 S 4.41 O 0.09 Cl 1.5 The raw material is 2.06 mol of Li 2 S, 1.5 mol LiCl, 0.47 mol P 2 S 5 and 0.03 mol In 2 O 3 .
[0074] Embodiment 13
[0075] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.7 P 0.9 In 0.1 S 4.35 O0.15 Cl 1.5 The raw material is 2.1 mol of Li 2 S, 1.5 mol LiCl, 0.45 mol P 2 S 5 and 0.05 mol In 2 O 3 .
[0076] Embodiment 14
[0077] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 In 0.0 2 S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw material is 2.02 mol of Li 2 S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P 2 S 5 and 0.01 mol In 2 O 3 .
[0078] Embodiment 15
[0079] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.52 P 0.99 Bi 0.0 1 S 4.485 O 0.015 Cl 1.5 The raw material is 2.01 mol of Li 2 S, 1.5 mol LiCl, 0.495 mol P 2 S 5 and 0.005 mol Bi 2 O 3 .
[0080] Example 16
[0081] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 Bi 0.0 2 S 4.47 O 0.03 Cl 1.5 The raw material is 2.02 mol of Li2 S, 1.5 mol LiCl, 0.49 mol P 2 S 5 and 0.01 mol Bi 2 O 3 .
[0082] Embodiment 17
[0083] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.62 P 0.94 Bi 0.0 6 S 4.41 O 0.09 Cl 1.5 The raw material is 2.06 mol of Li 2 S, 1.5 mol LiCl, 0.47 mol P 2 S 5 and 0.03 mol Bi 2 O 3 .
[0084] Embodiment 18
[0085] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 The raw material is 2.1 mol of Li 2 S, 1.5 mol LiCl, 0.45 mol P 2 S 5 and 0.05 mol Bi 2 O 3 .
[0086] Embodiment 19
[0087] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 Bi 0.0 2 S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw material is 2.02 mol of Li 2 S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P 2 S 5and 0.01 mol Bi 2 O 3 .
[0088] Embodiment 20
[0089] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.53 P 0.99 Mg 0.0 1 S 4.49 O 0.01 Cl 1.5 The raw material is 2.015 mol of Li 2 S, 1.5 mol LiCl, 0.495 mol P 2 S 5 and 0.01 mol of MgO.
[0090] Embodiment 21
[0091] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.56 P 0.98 Mg 0.0 2 S 4.48 O 0.02 Cl 1.5 The raw material is 2.03 mol of Li 2 S, 1.5 mol LiCl, 0.49 mol P 2 S 5 and 0.02 mol of MgO.
[0092] Embodiment 22
[0093] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.68 P 0.94 Mg 0.0 6 S 4.44 O 0.06 Cl 1.5 The raw material is 2.09 mol of Li 2 S, 1.5 mol LiCl, 0.47 mol P 2 S 5 and 0.06 mol of MgO.
[0094] Embodiment 23
[0095] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.8 P 0.9 Mg 0.1 S4.48 O 0.1 Cl 1.5 The raw material is 2.15 mol of Li 2 S, 1.5 mol LiCl, 0.45 mol P 2 S 5 and 0.1 mol of MgO.
[0096] Embodiment 24
[0097] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.56 P 0.98 Mg 0.0 2 S 4.48 O 0.02 Cl 1.3 Br 0.1 I 0.1 The raw material is 2.03 mol of Li 2 S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P 2 S 5 and 0.02 mol of MgO.
[0098] Comparative Example 1
[0099] The difference between this comparative example and Example 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The raw material is 2 mol of Li 2 S, 1.5 mol LiCl and 0.5 mol P 2 S 5 .
[0100] Comparative Example 2
[0101] The difference between this comparative example and Example 1 is that the solid electrolyte only includes sulfide electrolyte.
[0102] Comparative Example 3
[0103] The difference between this comparative example and Example 1 is that the sulfide electrolyte is in pure CO 2 The exposure time was 72h.
[0104] The composition and parameters of the sulfide electrolyte and the coating layer in the solid electrolyte of each embodiment and comparative example are shown in Table 1. Moreover, in one embodiment of the present invention, for example, the stability of the solid electrolyte to air in each embodiment and comparative example is tested, and the measurement results are shown in Table 1. Specifically, the ionic conductivity of the solid electrolyte is measured before and after exposure to humid air with a dew point temperature of -40° for 24 hours, and then the retention rate of the ionic conductivity after exposure for 24 hours is calculated.
[0105] Table 1. Parameters of solid electrolytes in Examples 1 to 24 and Comparative Examples 1 to 3
[0106]
[0107] In the present invention, performance tests were performed on all-solid-state batteries prepared using different solid electrolyte membranes in Examples 1 to 24 and Comparative Examples 1 to 3.
[0108] See also Figure 1 As shown, in one embodiment of the present invention, for example, the all-solid-state battery in Example 3 is subjected to a room temperature cycle performance test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V to obtain the capacity (CC) and coulombic efficiency (CE) at different cycle numbers. Figure 1 It can be seen that with the increase in the number of cycles, the attenuation trend of the battery CC is relatively gentle, and the battery CE does not fluctuate and stabilizes at around 100%, which indicates that the battery has good cycle performance.
[0109] Please refer to Table 2. In one embodiment of the present invention, for example, the all-solid-state batteries in Examples 1 to 24 and Comparative Examples 1 to 3 are subjected to a room temperature cycle stability test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V. The test is terminated when the battery capacity reaches 80% of the first cycle capacity State of Health (SOH), and the number of room temperature cycles of the battery is recorded. The recorded results are shown in Table 2.
[0110] Table 2. Test results of all-solid-state batteries in Examples 1 to 24 and Comparative Examples 1 to 3
[0111] Group Normal temperature cycle number (80% SOH) Example 1 1084 Example 2 1145 Example 3 1229 Example 4 1200 Example 5 1190 Example 6 814 Example 7 1168 Example 8 1043 Example 9 1129 Example 10 808 Embodiment 11 1186 Example 12 1090 Embodiment 13 1038 Embodiment 14 1086 Embodiment 15 794 Example 16 1168 Embodiment 17 1072 Embodiment 18 1020 Embodiment 19 1068 Embodiment 20 798 Embodiment 21 1152 Embodiment 22 1056 Embodiment 23 969 Embodiment 24 1052 Comparative Example 1 95 Comparative Example 2 595 Comparative Example 3 64
[0112] Please refer to Table 1 and Table 2. By comparing Examples 1-5, Comparative Example 2 and Comparative Example 3, it can be seen that as the sulfide electrolyte is exposed to pure CO 2With the increase of exposure time, the thickness of the coating layer gradually increases, and the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first gradually increases, and then gradually decreases, that is, the normal temperature cycle stability of the battery shows a trend of first increasing and then decreasing, which shows that the coating layer can improve the electrochemical stability of the solid electrolyte and its stability to air. However, since the conductivity of the lithium carbonate in the coating layer differs from that of the sulfide electrolyte by more than one order of magnitude, when the thickness of the coating layer is too large, it will greatly prevent the transmission of lithium ions, resulting in a serious decrease in the overall conductivity of the solid electrolyte, thereby affecting the cycle performance of the battery. Therefore, by controlling the thickness of the coating layer, both the stability of the solid electrolyte and the cycle performance of the battery can be taken into account.
[0113] Please refer to Table 1 and Table 2. Comparison of Examples 3, 6 to 8 shows that with the increase in the amount of Sb doped in the sulfide electrolyte, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. Comparison of Examples 10 to 13 shows that with the increase in the amount of In doped in the sulfide electrolyte, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. By comparing Examples 15 to 18, it can be seen that as the doping amount of the Bi element in the sulfide electrolyte increases, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the M element in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be taken into account.
[0114] As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 20 to 23 that as the doping amount of the Mg element in the sulfide electrolyte increases, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the E element in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be taken into account.
[0115] Refer to Table 1 and Table 2, and compare Examples 3 and 9, Examples 11 and 14, Examples 16 and 19, and Examples 21 and 24. When the doping amount of Sb, In, Bi or Mg in the sulfide electrolyte is the same, if Br and I are doped into the sulfide electrolyte, the retention rate of the ionic conductivity of the solid electrolyte will decrease, that is, the stability of the solid electrolyte to air will decrease, and the number of normal temperature cycles of the battery will also decrease, that is, the cycle performance of the battery will decrease. Therefore, by controlling the number of element types contained in X or Q in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be further improved.
[0116] Please refer to Table 1 and Table 2. By comparing Example 3, Example 11, Example 16, Example 21 and Comparative Example 1, it can be seen that when the sulfide electrolyte is not doped with Sb, Bi, In or Mg elements, the retention rate of the ionic conductivity of the solid electrolyte will be significantly reduced, that is, the stability of the solid electrolyte to air is very poor, and the number of cycles of the battery at room temperature is only 95, and there is almost no cycle performance, which shows that the Sb, Bi, In or Mg elements doped in the sulfide electrolyte can significantly improve the stability of the solid electrolyte to air and the cycle performance of the battery. Therefore, by controlling the type of M or E elements in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be improved.
[0117] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state batteries, and the all-solid-state battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state battery, and therefore includes the advantages of the above-mentioned all-solid-state battery, which will not be elaborated here.
[0118] In summary, the present invention proposes a solid electrolyte and its application. By providing a coating layer on the surface of the sulfide electrolyte, on the one hand, it can effectively prevent electrons from being transmitted between the sulfide electrolyte and the positive electrode material, avoid interfacial reaction between the sulfide electrolyte and the positive electrode material, improve the stability of the solid electrolyte to the positive electrode, thereby improving the cycle life, stability and safety of the all-solid-state battery; on the other hand, it can prevent the sulfide electrolyte from directly contacting with moisture and oxygen in the air, avoid the reaction of the sulfide electrolyte with moisture and oxygen in the air, improve the stability of the solid electrolyte to air, thereby further improving the cycle life of the battery.
[0119] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0120] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A solid electrolyte, characterized in that At least: Sulfide electrolytes; as well as A coating layer is disposed on the surface of the sulfide electrolyte, and the material of the coating layer includes lithium carbonate; Wherein, after the solid electrolyte is exposed to moist air with a dew point temperature of -40°C for 24 hours, the retention rate of ionic conductivity is 56% to 95%.
2. The solid electrolyte according to claim 1, characterized in that The chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from at least one of Cl, Br or I.
3. The solid electrolyte according to claim 2, characterized in that M is selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is 0 <b≤0.1。 4. The solid electrolyte according to claim 1, characterized in that The chemical formula of the sulfide electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.
5. The solid electrolyte according to claim 4, characterized in that E is Mg, Q is Cl, and the value range of g is 0.01≤g≤0.
1.
6. The solid electrolyte according to claim 1, characterized in that The coating layer has a thickness of 1 nm to 200 nm.
7. The solid electrolyte according to claim 1, characterized in that The solid electrolyte is obtained by the following method: providing a sulfide electrolyte; and The sulfide electrolyte is exposed to pure CO2 and heated to form a coating layer on the surface of the sulfide electrolyte to obtain the solid electrolyte.
8. The solid electrolyte according to claim 7, characterized in that The pressure of the pure CO2 is 0.01MPa to 10MPa, the exposure time of the sulfide electrolyte in the pure CO2 is 0.1h to 24h, and the heating temperature is 0 to 200°C.
9. An all-solid-state battery, characterized in that: At least: Positive electrode; Negative electrode; as well as A solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane comprises the solid electrolyte described in any one of claims 1-8.
10. An electronic device, characterized in that: Including the all-solid-state battery as described in claim 9.